1983
DOI: 10.7863/jum.1983.2.6.251
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative real-time ultrasonographic localization of pancreatic insulinoma: initial experience.

Abstract: Intraoperative localization of pancreatic insulinomas in four patients using a commercially available real-time scanner is described. Four tumors that were suspected preoperatively were confirmed and another that had not been suspected was identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
3

Year Published

1984
1984
2002
2002

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 6 publications
0
12
1
3
Order By: Relevance
“…O uso da ultra-sonografia intra-operatória para localização de insulinomas foi inicialmente descrito em 1982, por Lane e Coupland (7) . Desde então, vários autores têm descrito sua experiência, com resultados bastante satisfatórios (8,9) . Este método foi utilizado não só em tumores endócri-nos, como também em adenocarcinomas e em tumores benignos como o tumor sóli-do-cístico do pâncreas (tumor de Frantz), estudando características macroscópicas, extensão e relação com vasos e ductos pancreáticos, especialmente quanto à dilatação secundária destes e presença ou não de pequenos cálculos nos ductos (10,11) .…”
Section: Discussionunclassified
“…O uso da ultra-sonografia intra-operatória para localização de insulinomas foi inicialmente descrito em 1982, por Lane e Coupland (7) . Desde então, vários autores têm descrito sua experiência, com resultados bastante satisfatórios (8,9) . Este método foi utilizado não só em tumores endócri-nos, como também em adenocarcinomas e em tumores benignos como o tumor sóli-do-cístico do pâncreas (tumor de Frantz), estudando características macroscópicas, extensão e relação com vasos e ductos pancreáticos, especialmente quanto à dilatação secundária destes e presença ou não de pequenos cálculos nos ductos (10,11) .…”
Section: Discussionunclassified
“…Selective gastrin venous sampling from portal venous tributaries has been recommended to localize small tumors [76,83,84], but a recent study [85] demonstrated that it has equal sensitivity to imaging, with a lower specificity and a localized gradient that does not correlate with tumors being found at surgery. The usefulness of intraoperative ultrasonography is currently being evaluated to localize small tumors [86,87,89], and one study [88] suggests it will be useful in changing management in 10% of patients with ZES by identifying tumors not found by palpation and tumors with malignant extension previously thought to be localized.…”
Section: Diagnosis Of Zes Should Be Established By Measur-mentioning
confidence: 99%
“…Numerous procedures, including ultrasound, CT scanning, angiography, MRI scanning, selective gastrin sampling from portal venous tributaries, and intraoperative ultrasound, have been described for localizing gastrinomas [3,14,[73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90]. CT scanning with intravenous contrast is recommended as the initial imaging procedure; follow-up ultrasound and selective angiography should be performed if the CT scan is negative.…”
Section: Diagnosis Of Zes Should Be Established By Measur-mentioning
confidence: 99%
“…However, their small size and variable location within the pancreas can hinder tumor localization, as well as complicate surgical excision. Despite the very high percentage of insulinomas identified intraoperatively by experienced surgeons, as many as 27% of patients with biochemical and clinical evidence of hyperinsulinism have occult tumors at surgery [33,34]. In this situation the surgeon is likely to perform a "blind" distal pancreatectomy in the hope of identifying the lesion; however, this procedure is associated with significant morbidity and mortality and a high rate of persistent hyperinsulinism.…”
Section: Syndromesmentioning
confidence: 99%